2023
DOI: 10.1021/acs.jchemed.3c00591
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Formative Assessment Classroom Techniques (FACTs) to School Chemistry Teaching: Teachers’ Attitudes, Beliefs, and Experiences

Mária Babinčáková,
Mária Ganajová,
Paweł Bernard

Abstract: This paper presents teachers’ perspectives and experiences with the implementation of formative assessment (FA) into chemistry lessons at the secondary school level through Formative Assessment Classroom Techniques (FACTs). The research had a qualitative character and was based on semistructured interviews focused on: the definition and previous use of FA, implementation experience, and teachers’ beliefs, attitudes, and abilities. The research describes five caseschemistry teachers participating in a professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Alternatively, inquiry-based teaching incorporates formative assessment methods (Bernard et al, 2019;Babinčáková et al, 2020;Babinčáková et al, 2023). Students actively participated in their designed experiments within self-created groups.…”
Section: A) Teaching and Learning Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, inquiry-based teaching incorporates formative assessment methods (Bernard et al, 2019;Babinčáková et al, 2020;Babinčáková et al, 2023). Students actively participated in their designed experiments within self-created groups.…”
Section: A) Teaching and Learning Approachmentioning
confidence: 99%
“…The best practices in the formative assessment conducted properly through teacher collaboration would support problem-solving aptitude (Abell & Sevian, 2020). Giving useful feedback is seen as beneficial in implementing FACTs in the classroom, which supports these skills (Babinčáková et al, 2020;Babinčáková et al, 2023). Furthermore, the teachers also suggested that a crucial part of problem-solving skills is that students must be able to make a self-assessment and identify their weaknesses.…”
Section: C) Problem-solvingmentioning
confidence: 99%
See 3 more Smart Citations